Moral Hazard and Cash Benefits in Long-Term Home Care - Bernard van den Berg; Wolter H.J. Hassink (Institute for the Study of Labor (IZA), 2005)
This paper tests empirically for ex-post moral hazard in a system based on demand-side subsidies. In the Netherlands, demand-side subsidies were introduced in 1996. Clients receive a cash benefit to purchase the type of home care (housework, personal care, support with mobility, organisational tasks or social support) they need from the care supplier of their choice (private care provider, regular care agency, commercial care agency or paid informal care provider). Furthermore, they negotiate with the care supplier about price and quantity. Our main findings are the following. 1) The component of the cash benefit a client has no residual claimant on, has a positive impact on the price of care. 2) In contrast, the components of the cash benefit a client has residual claimant on, have no or a negative impact on the price of care. Both results point at the existence of ex-post moral hazard in a system of demand-side subsidies.
Keywords: I10; 330; long-term care; cash benefits; consumer directed services; demand-side subsidies; direct payments; moral hazard